2007
DOI: 10.1177/112067210701700206
|View full text |Cite
|
Sign up to set email alerts
|

A 1-Year Study to Compare the Efficacy and Safety of Once-Daily Travoprost 0.004%/Timolol 0.5% to Once-Daily Latanoprost 0.005%/Timolol 0.5% in Patients with Open-Angle Glaucoma or Ocular Hypertension

Abstract: Travoprost 0.004%/timolol 0.5% ophthalmic solution produced mean IOP levels that are statistically noninferior to latanoprost 0.005%/timolol 0.5% ophthalmic solution. Furthermore, at 9:00 AM, 24 hours after dosing, IOP was statistically lower for travoprost 0.004%/timolol 0.5% pooled across all visits. Travoprost 0.004%/timolol 0.5% fixed combination ophthalmic solution is an effective treatment for reducing IOP and it is safe and well-tolerated in patients with OAG or OH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 15 publications
0
21
0
2
Order By: Relevance
“…33 We believe that such an evaluation meets our inclusion criteria of a prostaglandin versus an inert control as the prostaglandin effect here is the same relative effect as if it were prostaglandin versus nothing. We have conducted a sensitivity analysis to examine if our findings would differ on the primary outcome of IOP-lowering effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 We believe that such an evaluation meets our inclusion criteria of a prostaglandin versus an inert control as the prostaglandin effect here is the same relative effect as if it were prostaglandin versus nothing. We have conducted a sensitivity analysis to examine if our findings would differ on the primary outcome of IOP-lowering effects.…”
Section: Discussionmentioning
confidence: 99%
“…We found several instances where the primary outcomes were not significantly different, but the authors reported them as clinically important in their conclusions. 33 Further, on average, the trials included in our analysis were small. There is a clear need for minimum sample sizes in equivalence trials of PGAs to avoid wasted resources and potentially spurious outcomes.…”
Section: Dovepressmentioning
confidence: 99%
“…Prostaglandin analogs for ocular hypertension and glaucoma FCLT (16.7 to 17.7 mmHg), 100 supported by a retrospective, cross-sectional study. 210 However, ocular hyperemia rates were higher with FCTT (15%) compared with FCLT (2.5%).…”
mentioning
confidence: 99%
“…210 However, ocular hyperemia rates were higher with FCTT (15%) compared with FCLT (2.5%). 100 Compared with FCDT, mean pooled diurnal IOP was significantly lower with FCTT (16.5 ± 0.23 mmHg vs 17.3 ± 0.23 mmHg; P = 0.011) in a randomized-control, parallel, double-masked trial (n = 319). 209 FCTT produced mean IOP reductions of 35.3% to 38.5%, FCDT reduced IOP 32.5% to 34.5%.…”
mentioning
confidence: 99%
See 1 more Smart Citation